SELF CONFIDENCE AND TEACHING COMPETENCY AMONG TEACHER EDUCATORS - N.Vivekananda, Dr.R.Meenakshi (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The abstract emphasizes the pivotal role of teachers in national development, stressing that a positive outlook enhances their productivity and, consequently, the quality of education they provide. It underscores the importance of occasional confidence boosts for teachers to effectively tackle new challenges in education. This necessitates positive modifications to their teaching philosophies. The abstract posits a reciprocal relationship between teachers' self-confidence and their attitudes towards instruction. It asserts that teachers' teaching philosophies and levels of self-assurance significantly impact students and the learning environment. Confidence and a positive attitude towards teaching are posited as facilitators of improved learning outcomes. Central to the abstract is the call for educators and decision-makers to create environments conducive to enhancing teachers' self-confidence and fostering positive attitudes towards their profession. It advocates for research focused on understanding and enhancing the critical factors of teachers' self-confidence and attitudes towards teaching. In essence, the abstract argues that teachers play a crucial role in shaping the future through education. Their confidence and outlook directly influence the quality of teaching and learning experiences. By supporting teachers with the right environment and encouragement, policymakers can enhance educational outcomes and contribute positively to national development.